Evaluating the materials used for hydrogen production based on photoelectrochemical technology - Mohammdreza Nazemzadegan; Roghayeh Ghasempour (Center of Biomass & Renewable Energy, Diponegoro University, 2019)
Hydrogen as a CO2-free fuel has been considered as a serious alternative for problematic fossil fuels in recent decades Photoelectrochemical (PEC) water splitting is a developing solar-based technology for hydrogen production. In this study, some possible options for upgrading this technology from R&D stage to prototype stage through a material selection approach is investigated. For these purpose, TOPSIS algorithm through a multi criteria decision making (MCDM) approach was utilized for evaluating different (PEC)-based hydrogen production materials. TiO2, WO3 and BiVO4 as three semiconductors known for their PEC application, were selected as alternatives in this decision-making study. After defining a set of criteria, which were assessed based on similar studies and experts' visions, a group of ten PEC-experts including university professors and PhD students were asked to fill the questionnaires. The eight criteria considered in this study are include